2008
DOI: 10.1016/j.mechatronics.2008.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Large throw magnetic microactuator

Abstract: a b s t r a c tThe design and fabrication of an electromagnetic MEMS actuator capable of repeatedly switching over a gap length of 100 lm is presented. The device is to be used as a switch for radio-frequency (RF) circuits. It is based on a potcore type electromagnet and a mover suspended on a microbeam. The device was first modelled and optimised using a finite element analysis and then microfabricated. The ultra thick, negative photoresist, SU-8, was used extensively throughout the construction as: (i) an el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The AFE phase can be induced into ferroelectric (FE) phase under the external sufficient electric field. For the unit cell of the FE phase is larger than that of AFE phase, so the volume of the material changes together with the phase transition [2,3]. W.Y Pan et al [4,5] reported that the strain of (Pb,La)(Zr,Ti,Sn)O 3 antiferroelectric ceramics can reach 0.85%.…”
Section: Intorductionmentioning
confidence: 99%
“…The AFE phase can be induced into ferroelectric (FE) phase under the external sufficient electric field. For the unit cell of the FE phase is larger than that of AFE phase, so the volume of the material changes together with the phase transition [2,3]. W.Y Pan et al [4,5] reported that the strain of (Pb,La)(Zr,Ti,Sn)O 3 antiferroelectric ceramics can reach 0.85%.…”
Section: Intorductionmentioning
confidence: 99%
“…For RF MEMS, the large displacement could ensure effective isolation for the signal transformation for operation in the region of 10 GHz as reported in [10]. A variety of MEMS switches, including electrothermal [10], electrostatic [11], and electromagnetic [12,13,14,15,16,17,18,19,20], were reported. The electrothermal microswitch usually tends to respond slowly; as a result, its application is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The electromagnetic microactuator mainly consists of the microcoil and the moving membrane, which were fabricated on different wafers, separately. Then, the permanent magnet, membrane, and microcoil were assembled by bonding or via a manual process [15,16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…The planar electromagnetic actuator, especially that made by micro-fabrication technology, has the advantages of small volume and suitability for planar integration. In recent years, the method of integrating a planar coil with a permanent magnet as a micro-actuator has been widely used in micropumps, microvalves and other microelectromechanical systems (MEMS) devices because they can obtain large displacements and a big driving force in the case of a low applied voltage [ 22 , 23 , 24 ]. Tilmans et al [ 22 ] introduced a fully integrated electromagnetic microrelay.…”
Section: Introductionmentioning
confidence: 99%